Machinery, Monstrosity, and Bestiality: An Analysis of Repulsion in Kierkegaard's Practice in Christianity - Johnson, Ryan J. (Heythrop journal, 2014)
In reaction to a particularly scathing review of his Practice in Christianity, Kierkegaard postulated what he called a ‘preacher-machine.’ As we will see, the preacher-machine is only one type of character-machine, for, in Practice in Christianity, there are five other such machines. Starting up these character-machines will allow for an analysis of the repulsion of the God-man, Christ himself. This repulsion is important because Kierkegaard claims that it is the condition for the emergence of faith. After discussing repulsion, Kierkegaard will locate a singular mistake of Christendom, which will allow him to offer his remedy to this problem. In doing so, I will claim, Kierkegaard makes a particularly forceful claim about the true status of Christianity. We begin by attempting an articulation of a definition of monstrosity before setting the scene of these six machines.